2016
DOI: 10.1111/1462-2920.13352
|View full text |Cite
|
Sign up to set email alerts
|

Type II NADH:quinone oxidoreductase family: phylogenetic distribution, structural diversity and evolutionary divergences

Abstract: Type II NADH:quinone oxidoreductases (NDH-2s) are membrane proteins, crucial for the catabolic metabolism, because they contribute to the maintenance of the NADH/NAD balance. In several pathogenic bacteria and protists, NDH-2s are the only enzymes performing respiratory NADH:quinone oxidoreductase activity. For this reason and for being considered absent in mammals, NDH-2s were proposed as suitable targets for novel antimicrobial therapies. We selected all sequences of genes encoding NDH-2s from fully sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…All of these organisms carry genes encoding complex I (NADH:ubiquinone reductase, EC 1.6.5.3). Some members of Hydrogenovibrio carry genes encoding alternative (type II) NADH:ubiquinone reductase (EC 1.6.5.9), which is common among ‘Proteobacteria’ (Marreiros et al ., ), though not among the autotrophic organisms surveyed here (Supporting Information Table S4). Type II NADH:ubiquinone reductase oxidizes NADH without directly contributing to proton potential, which may function to maintain cellular NADH/NAD + ratios (Kerscher et al ., ).…”
Section: Resultsmentioning
confidence: 90%
“…All of these organisms carry genes encoding complex I (NADH:ubiquinone reductase, EC 1.6.5.3). Some members of Hydrogenovibrio carry genes encoding alternative (type II) NADH:ubiquinone reductase (EC 1.6.5.9), which is common among ‘Proteobacteria’ (Marreiros et al ., ), though not among the autotrophic organisms surveyed here (Supporting Information Table S4). Type II NADH:ubiquinone reductase oxidizes NADH without directly contributing to proton potential, which may function to maintain cellular NADH/NAD + ratios (Kerscher et al ., ).…”
Section: Resultsmentioning
confidence: 90%
“…The low NADP + /NADPH affinity can be explained by the structure of NDH-2 with NAD + /NADH bound (discussed later), by unfavorable interactions between the side chain of E198 and the adenine nucleotide phosphate. Indeed, sequence analyses suggests that the majority of NDH-2 variants contain Glu or Asp at this position and so react only with NADH2, and the corresponding Glu to Gln mutation in Agrobacterium tumefaciens NDH-2 was demonstrated to change its specificity towards NADPH23.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in NDH-1 (respiratory complex I, which catalyzes the same reaction in animals and many other species) catalysis by NDH-2 is not used to support the proton motive force that drives ATP synthesis, so its catalysis is highly exergonic and essentially irreversible. NDH-2 is also much smaller and simpler in structure than complex I – it comprises only a single subunit and one flavin redox cofactor12. Consequently, it has been explored as a gene therapy for human complex I disorders, to relieve the accumulation of NADH and decrease reactive oxygen species (ROS) production3456.…”
mentioning
confidence: 99%
“…1B) is a non-classical RS enzyme which uses reductants (sulphide, sulphite, or cyanide) which are not normally formed under aerobic metabolism in typical eukaryotes (Hildebrandt and Grieshaber, 2008). Some distant homology is observed between NDH2s and apoptosis-inducing factor (AIF), and apoptosis-inducing factor-like proteins (Elguindy and Nakamaru-Ogiso, 2015;Marreiros et al, 2016). Moreover, it was shown that NDH2 from the budding yeast Saccharomyces cerevisiae is able to promote apoptosis (Li et al, 2006;Cui et al, 2012), while AIF can operate as a NADH dehydrogenase (Elguindy and Nakamaru-Ogiso, 2015).…”
Section: Introductionmentioning
confidence: 99%